2014
DOI: 10.1007/s11031-014-9426-1
|View full text |Cite
|
Sign up to set email alerts
|

Emotion as a necessary component of threat-induced death thought accessibility and defensive compensation

Abstract: Terror management theory presents an account of how the avoidance of the potential anxiety accompanying knowledge of one's inevitable mortality motivates a vast array of human behaviors. However, in practice, evidence from one of the hypotheses designed to test this account-the death thought accessibility (DTA) hypothesis-has been purely cognitive. The goal of the present research was to examine the role of emotion in this process. Participants were presented with existentially threatening stimuli under experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 47 publications
1
23
0
2
Order By: Relevance
“…Perhaps thinking about planning one's own funeral evokes much stronger negative emotions than does a will, leading consumers to avoid making the purchase to minimize or eliminate negative emotions in their decision‐making processes as some prior research suggests (e.g., Anderson, ; Drolet & Luce, ). This conjecture is somewhat supported by Gordon and Arian (, p. 196), who concluded that when an experience makes individuals feel very threatened, the decision making process is “dominated by emotion ,” but when the threat is perceived as low, “ both emotions and logic ” play a role in the decision process [emphasis in the original], and by Webber et al () who found that eliminating emotion from a threatening situation reduced thoughts of death.…”
Section: Studymentioning
confidence: 94%
“…Perhaps thinking about planning one's own funeral evokes much stronger negative emotions than does a will, leading consumers to avoid making the purchase to minimize or eliminate negative emotions in their decision‐making processes as some prior research suggests (e.g., Anderson, ; Drolet & Luce, ). This conjecture is somewhat supported by Gordon and Arian (, p. 196), who concluded that when an experience makes individuals feel very threatened, the decision making process is “dominated by emotion ,” but when the threat is perceived as low, “ both emotions and logic ” play a role in the decision process [emphasis in the original], and by Webber et al () who found that eliminating emotion from a threatening situation reduced thoughts of death.…”
Section: Studymentioning
confidence: 94%
“…Ernest Becker (1973) argued that conscious and subconscious death awareness, and subsequent anxiety, is a central driver of human behavior. More recently, cognitive science and psychology researchers have confirmed that negative emotions, particularly fear, anxiety, and foreboding associated with one's mortality awareness, generate motivated cognition and are highly influential (Raghunathan and Pham 1999, Lerner and Keltner 2000, Pham 2007, Abeyta et al 2014, Webber et al 2015, Wolfe and Brooks 2016). …”
Section: Emotions and Decision Makingmentioning
confidence: 99%
“…We focused on this measure, as it appeared more sensitive to meaning violations than the grammar task (i.e., larger average effect size across previous MMM studies; Cohen's d of .81 vs. .66). Furthermore, this measure has been used under the auspices of both TMT and MMM as an indicator of meaning restoration following MS (Rosenblatt, Greenberg, Solomon, Pyszczynski, & Lyon, 1989), a variety of minimal meaning threats (Proulx & Heine, 2008;Randles et al, 2013), and a threat to highly valued worldview beliefs (Webber et al, 2015). We expected to find increased meaning affirmation in response to a meaning threat, particularly for individuals high in PNS.…”
Section: Studymentioning
confidence: 99%
“…According to this hypothesis, if a psychological structure functions to protect individuals from thoughts of death, then threatening that structure should temporarily weaken its ability to keep thoughts of death at bay, leading to an immediate increase in the accessibility of death thoughts. As such, experiments have found higher levels of DTA after threatening people's national identity (Schimel, Hayes, Williams, & Jahrig, 2007), core religious beliefs (Friedman & Rholes, 2007;Webber et al, 2015), and bases for self-esteem (Hayes, Schimel, Faucher, & Williams, 2008;Hayes, Schimel, Arndt, & Faucher, 2010 for a review).…”
mentioning
confidence: 99%
See 1 more Smart Citation